2018
DOI: 10.1089/lgbt.2017.0220
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Differences in Modifiable Risk Factors for Cardiovascular Disease and Cardiovascular Disease Diagnoses in Men

Abstract: Gay-identified and heterosexual-identified MSM demonstrated similar CVD risk to exclusively heterosexual men, whereas bisexual-identified men had elevations in several risk factors. Future directions for sexual minority health research in this area and the need for CVD and mental health screenings, particularly in bisexual-identified men, are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 58 publications
(58 reference statements)
2
42
1
1
Order By: Relevance
“…For instance, a recent analysis of data from the National Health and Nutrition Examination Survey detected higher rates of objectively measured obesity and hyperglycemia in sexual minority women and bisexual men. 15,16 Objective measures of CVD risk factors (such as body mass index, physical activity, diabetes, hypertension and lipids) should be integrated into CVD research with sexual minorities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent analysis of data from the National Health and Nutrition Examination Survey detected higher rates of objectively measured obesity and hyperglycemia in sexual minority women and bisexual men. 15,16 Objective measures of CVD risk factors (such as body mass index, physical activity, diabetes, hypertension and lipids) should be integrated into CVD research with sexual minorities.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found that self-identified gay and bisexual men were both at increased risk for HIV compared to self-identified heterosexual men who had never had sex with men. Specifically, data from a nationally representative sample revealed that 17.4% of selfidentified gay men and 7.7% of self-identified bisexual men were HIV-positive compared to only 0.3% of self-identified heterosexual men who had never had sex with men (Caceres et al, 2018). Similar to the findings for MSMW reviewed above, these findings indicate that, while self-identified gay men experience the greatest burden of HIV infection, self-identified bisexual men are also disproportionately affected by HIV compared to self-identified heterosexual men who have never had sex with men.…”
Section: Prevalence Of Hiv/sti Among Bisexual Menmentioning
confidence: 99%
“…Despite the lack of research on HIV/STI among bisexual men, the available evidence indicates that, similar to gay men, bisexual men are also at increased risk for HIV and other STI compared to heterosexual men (Caceres et al, 2018;Jeffries, 2010). However, efforts to prevent HIV/STI have largely overlooked bisexual men as a population in need of targeted services.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, a recent analysis of population-based data found that bisexual men had 2 to 3 times higher odds of obesity, hypertension, and diabetes than heterosexual men. 11…”
Section: Purposementioning
confidence: 99%